Evaluation of drug services based on prescription indicators and patient care according to who at the hospital general practitioner (GP) outpatient clinic in Depok, Indonesia - Syafhan, Nadia Farhanah; Risni, Hindun Wilda; Salsabila, Azzahra Fahira; Purnama Putri, Raden Jacinda Yasmin; Prasetyaningrum, Marchen (Faculty of Pharmacy, Universitas Pancasila, 2025)
The World Health Organization (WHO) has developed prescription and patient care indicators, accompanied by optimal benchmarks, aimed at promoting the rational and optimal medicine use. This study aims to evaluate drug services utilizing WHO prescription and patient care indicators at the hospital General Practitioner (GP) outpatient clinic. The research was conducted retrospectively for prescription indicators, consisting of 1505 prescriptions totaling 4647 medication items administered for 804 individuals between January and December 2022. Prospective data collection to evaluate patient care was conducted from April to May 2023. Evaluation of WHO prescription indicators yielded the following results: the average number of drugs prescribed per patient was 3.09 ± 2.00; the percentage of drug prescribed by generic drug names was 47.47%; the percentage of antibiotic prescriptions was 5.46%; the percentage of injectable drug prescriptions was 6.80%; and the percentage of prescriptions in accordance with the national formulary was 75.91%. The percentages of antibiotic and injectable drug prescriptions met the optimal WHO prescription values. In terms of patient care, the results showed that the average duration of a medical consultation was 12.44±8.1 minutes, the average duration of a drug dispensing was 45.65±28.8 minutes, 96.25% of the drugs were dispensed appropriately, 100% of the drugs were labeled adequately, and 78.78% of the patients were knowledgeable. Age (p=0.111) and gender (p=0.075) showed no significant correlation with patient knowledge. There was a significant relationship between education level (p=0.014) and patient knowledge. Prescription and patient care indicators are aspects of improvement to meet the optimal benchmarks according to WHO standards.